How does the educational background of cultural and creative organization founders influence intellectual capital and business models? : Evidence from the archaeological field - Vignieri, Vincenzo (Piccola Impresa / Small Business, 2025)
Purpose: This work investigates how the educational background of founders of cultural and creative organizations affects the relationship between intellectual capital and business models. Design/methodology/approach: A narrative literature review revealed a lack of studies in arts and humanities focusing on the relationship between intellectual capital and business models. The empirical investigation involved three case studies of three SMEs operating in the archaeological field, demonstrating that educational background significantly influences these relationships. Findings: The analysis identifies four key factors: creativity, network relationships, cross-disciplinary competencies, and adaptability to new technologies. Firstly, creativity serves as a driving force in the early stages of a start-up. Secondly, strong network relationships can provide access to external knowledge and resources, enhancing key assets. Thirdly, collaboration with partners enables organizations to adapt to evolving conditions, such as technological advancements, impacting both human and structural capital. Lastly, cross-disciplinary competencies allow for a multidisciplinary approach to problem-solving, fostering internal skill development. The findings suggest that educational background equips SMEs founders with the tools to create a compelling value proposition by leveraging cultural and creative organizations intellectual capital. Practical and social implications: Higher education institutions can encourage entrepreneurship by involving students in knowledge-transfer projects, like academic spin-offs. Originality of the study: The study provides insights into four directions associated with the effects of cultural and creative organizations founders educational background on the relationships between intellectual capital and business model.